Systematic review of parenting style and children's emotional intelligence: recent updates on Western and non- Western families - Mousavi, Azadeh; Juhari, Rumaya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Extant literature highlights certain comparisons between the effect of demanding parenting style in non-Western families (Muslims and non-Muslims) and that of the democratic type of parenting in Western counties on emotional intelligence, which contributes to improvements in mental health. A systematic review was conducted on original published articles using ‘parenting style’ and ‘emotional intelligence’ as keywords. Initial data collected from Google Scholar, Science Direct, Web of Science and PubMed were searched using the Rayyan software (26) for relevant articles written in English. However, after applying the inclusion and exclusion criteria, only 28 articles (14 from each type of society, that is, non-Western and Western) were included in the review. Consequently, the review found that social environment, cultural, religious and economic conditions significantly predicted emotional intelligence.